Validitas dan Reliabilitas Alat Ukur Self-Control pada Siswa Kecanduan Media Sosial - Ridna Shafira; Yana Nazela Ilma; Tengku Havidz Syahputra; Sondang Silaban; Suaidah Lubis (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to examine the validity and reliability of a self-control measurement instrument among senior high school students (SMA/MA) in Medan City. The need for a precise instrument arises from the high intensity of social media use among adolescents, which often leads to addictive behaviors and reduced self-regulation. This research represents the initial phase of a Research and Development (R&D) process, with a specific focus on psychometric evaluation of the instrument. The research subjects consisted of 50 students from grades X, XI, and XII, selected using a survey approach. Data were collected using a self-control scale comprising 12 statement items developed based on three dimensions, namely behavioral control, cognitive control, and decision control. Data analysis was conducted through validity testing using the Pearson Product Moment correlation technique and reliability testing using Cronbach’s Alpha. The validity test results indicated that 11 out of the 12 items met the validity criteria, with item-total correlation coefficients ranging from 0.312 to 0.684, exceeding the critical value of 0.279, while one item was found to be invalid. Furthermore, the reliability analysis produced a Cronbach’s Alpha coefficient of 0.707, which falls within the acceptable reliability range. Based on these findings, it can be concluded that the self-control scale demonstrates adequate item discrimination and internal consistency, making it suitable for use.